A review on natural way of vaccination: Plant derived edible vaccines - Arif Khan; Asad Khan; Irfan Khan; Muhammad Aamir Shehzad; Waqar Ali; Atif Muhammad; Muhammad Akif (Journal of Vaccines and Immunology - Peertechz Publications, 2019)
Immunizing human or animals with edible plants is an evolving tool that seems to grip countless potential. The selected/desired antigen of pathogens (HIV, tuberculosis etc) are inserted to the selected host plant by transformation technique to form a transgenic plant. Edible vaccines grip countless promise as a profi table, easily managing, can be store easily, unlikely or unable to fail and sociocultural gladly sustainable, particularly for the poor emerging nations. An edible vaccine takes the place of sore immunization methods. Compare to conventional vaccine, edible vaccine is inexpensive, needle free, eradicates the requirement for preservation, harmless, may be stored nearby to place of usage, and deliver mucosal and complete immunity.